Safety and efficacy of simultaneous bilateral primary combined trabeculotomy-trabeculectomy for developmental glaucoma - Mandal Anil; Bhatia Prashant; Gothwal Vijaya; Reddy Vijay; Sriramulu P; Prasad M; John Rajesh; Nutheti Rishita; Shamanna B (Indian Journal of Ophthalmology, 2002)
Purpose: To establish the safety and efficacy of simultaneous bilateral primary combined trabeculotomy-trabeculectomy for developmental glaucoma. Methods: We studied 109 consecutive patients who underwent planned simultaneous bilateral primary combined trabeculotomy-trabeculectomy for developmental glaucoma by a single surgeon from January 1990 through December 1999. The main outcome measures were postoperative intraocular pressure (IOP), corneal clarity and diameter, visual acuity, bleb characteristics, time of surgical failure and complications. Postoperative complications including endophthalmitis and anaesthetic morbidity and mortality were also analysed. Results: The series consisted of 218 primary combined trabeculotomy-trabeculectomy surgeries during 109 anaesthesias. The mean follow-up period was 16.33 ± 16.22 months. The IOP reduced from 26.4 ± 5.9 mmHg to 13.5 ± 4.5 mmHg, with a mean percentage reduction of 46.2 ± 23.7 (P < 0.0001). The success (IOP < 16 mmHg) probabilities were 90.9%, 88.0% and 69.3% at first, second and third year respectively (Kaplan-Meier analysis). The success probability of 69.3% obtained at third year was maintained till 6 years of follow-up. One hundred and sixty six (76.1%) eyes had significant corneal oedema. Postoperatively, the cornea cleared in 93 (57.8 %) eyes. Clinically, well functioning blebs were present in 114 of 171 eyes (66.6%). Postoperatively, 18 (8.3%) eyes developed shallow anterior chamber and 6 (33.3%) of them required surgical reformation. There was no incidence of endophthalmitis or any other sight-threatening complication. Of the anesthetic complications, apnea occurred in 17 (15.6%) patients and all were successfully resuscitated. The most serious post-anaesthetic complication was cardio-pulmonary arrest that occurred 5 hours postoperatively following aspiration during feeding in one child; this child could not be resuscitated. Two children had delayed recovery (2 and 4 hours respectively). The child who had delayed recovery by 2 hours survived and has completed 3 years of follow-up while the other child expired 48 hours later. Conclusion: Simultaneous bilateral primary combined trabeculotomy-trabeculectomy is safe and effective for developmental glaucoma. It obviates the need for long second anaesthesia with its attendant risks. It offers several other benefits to the patients and families